Welfare Through Competence: A Framework for Animal-Centric Technology Design - Webber, Sarah; Cobb, Mia L.; Coe, Jon (Frontiers in Veterinary Science, 2022)
Digital technologies offer new ways to ensure that animals can lead a good life in managed settings. As interactive enrichment and smart environments appear in zoos, farms, shelters, kennels and vet facilities, it is essential that the design of such technologies be guided by clear, scientifically-grounded understandings of what animals need and want, to be successful in improving their wellbeing. The field of Animal-Computer Interaction proposes that this can be achieved by centring animals as stakeholders in technology design, but there remains a need for robust methods to support interdisciplinary teams in placing animals’ interests at the heart of design projects. Responding to this gap, we present the Welfare through Competence framework, which is grounded in contemporary animal welfare science, established technology design practices and applied expertise in animal-centred design. The framework brings together the “Five Domains of Animal Welfare” model and the “Coe Individual Competence” model, and provides a structured approach to defining animal-centric objectives and refining them through the course of a design project. In this paper, we demonstrate how design teams can use this framework to promote positive animal welfare in a range of managed settings. These much-needed methodological advances contribute a new theoretical foundation to debates around the possibility of animal-centred design, and offer a practical agenda for creating technologies that support a good life for animals.